Designing inclusive educational games: accessibility rubric - Cezarotto, Matheus Araujo; LaTasha Armstrong, Amanda (InfoDesign, 2023)
Accessibility is an essential component of inclusive design. Through accessibility affordances, developers and design teams can allow players with various needs (vision, hearing, motor, and cognitive) to use any given educational game to its fullest purpose while enjoying the experience, and educators can ensure all students engage in digital activities. Despite the recent increase in accessibility efforts, it can still be challenging for design teams to evaluate accessibility quality in digital educational games. Educational games have an extra layer that aims to promote learning of specific content, meaning its accessibility features have to allow learners to receive and process the content of information. This study proposes an applied and research-based rubric to discuss accessibility quality in educational games. The rubric is designed to support the design process with reflective guiding questions to address educational accessibility challenges.